Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.11604/pamj.2014.19.18.4445
|View full text |Cite
|
Sign up to set email alerts
|

Les perdus de vue en radiothérapie: expérience de l’Institut National d’Oncologie au Maroc

Abstract: Les perdus de vue (PDV) sont toute personne incluse dans un programme et dont on est sans nouvelles depuis six mois. L'objectif de cette étude est de fournir une description objective du problème des malades PDV au service de radiothérapie à l'Institut National d'Oncologie (INO), elle permet d’étudier l'impact des facteurs socio-économiques, démographiques et ceux liés à la maladie entraînant l'abandon du traitement par le patient. Nous avons réalisé une étude rétrospective de 77 patients PDV parmi 2254 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Our results are consistent with those of other authors who found that compliance with management strategies is driven by having a good health care delivery system. 1 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of other authors who found that compliance with management strategies is driven by having a good health care delivery system. 1 , 19 …”
Section: Discussionmentioning
confidence: 99%